2016
DOI: 10.1590/0104-07072016003210015
|View full text |Cite
|
Sign up to set email alerts
|

Managers' Discourse About Information and Knowledge Related to Directly Observed Treatment of Tuberculosis

Abstract: Qualitative study that aimed to analyze the discourse of 15 district managers about knowledge and information related to the transfer of the Directly Observed Treatment of Tuberculosis policy in the city of João Pessoa, Paraíba, Brazil. The empiric material, collected in May and June 2013 through interviews, was analyzed according to Michel Pêcheux's Discourse Analysis. Despite contradictions, misunderstandings and silences observed in some discourse about this policy, the interviewees value the matricial supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…A similar result was obtained in a study conducted in João Pessoa, Paraíba, in which the managers showed a lack of knowledge about this subject, and also in a context of DOT transfer, culminating in a significant weakening in the development of TB control actions 9 .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…A similar result was obtained in a study conducted in João Pessoa, Paraíba, in which the managers showed a lack of knowledge about this subject, and also in a context of DOT transfer, culminating in a significant weakening in the development of TB control actions 9 .…”
Section: Resultssupporting
confidence: 78%
“…However, low adherence and incorporation of this policy in primary care (PC) services are still found, along with a deficit by the municipal and state authorities regarding the linkage between demographic context, planning, and financing of programs designed to reduce costs generated by TB 9 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the ability to reconstruct, adapt, re-contextualize and reassemble acquired knowledge according to local needs and specificities becomes a key element of the DOT policy transfer process 12 and tends to be strengthened by stimulus and encouragement. Therefore, when health professionals get close to the indifference, raising doubts about the use of motivational strategies for the coordination of the tuberculosis program, precedents are opened to consider the possibility of disrupting this constructivist and innovative logic, with repercussions on its productive chain, on creative practice and on the TB control itself.…”
Section: Discussionmentioning
confidence: 99%
“…Another point concerns the fact that the treatment is not limited to simply monitoring the medication intake by the health professional, but it also involves other aspects such as qualified listening, strengthening of ties with the team and also the monitoring of adverse reactions, among others. 12 Regarding this last aspect, from the point of view of Innovation, its possible to observe the recognition by the health professionals of the importance of elaborating an individual care plan for the TB patient. In fact, a unique, personalized approach strengthened by listening and effective bond with TB patients and their families not only works as a possibility to better identify needs and to plan interventions, but also as a strategy for patient empowerment and an important assumption to promote health care based on the National Humanization Policy.…”
Section: Discussionmentioning
confidence: 99%
“…The decentralization of technical actions for TB control has not been homogeneous, differing according to the different contexts and scenarios. Therefore, managers must formulate innovative and decisive strategies for the establishment of an efficient process of Policy Transfer of the Tuberculosis Control Program Policy aimed at the sustainability and coordination of actions between the different levels of care and management of the health system, based on the priorities listed in each context (5) .…”
Section: Introductionmentioning
confidence: 99%